1998
DOI: 10.1007/s001040050424
|View full text |Cite
|
Sign up to set email alerts
|

Multimodale Therapie bei Tumoren des oberen Gastrointestinaltrakts

Abstract: Adjuvant and neoadjuvant therapeutic principles have in recent years received increasing attention in the management of patients with carcinoma of the upper gastrointestinal tract. A series of randomized prospective trials has demonstrated that adjuvant postoperative radiation or chemotherapy does not result in a convincing survival advantage after complete tumor resection in gastric or esophageal cancer. The available data on the role of neoadjuvant preoperative therapy in these patients as yet permit no conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
2
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 29 publications
0
26
2
4
Order By: Relevance
“…A multimodal therapy concept in patients with locally advanced Barrett's carcinoma is still under discussion, because many studies have shown that only patients who respond to a neoadjuvant chemotherapy have a survival benefit (9)(10)(11). In these patients, a neoadjuvant therapy results in a downsizing and a downstaging of the tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multimodal therapy concept in patients with locally advanced Barrett's carcinoma is still under discussion, because many studies have shown that only patients who respond to a neoadjuvant chemotherapy have a survival benefit (9)(10)(11). In these patients, a neoadjuvant therapy results in a downsizing and a downstaging of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…More than 50% of patients present with locally advanced disease (5)(6)(7). In these patients, neoadjuvant chemotherapy seems to increase the chance for a curative resection and enhance survival in responding patients (8)(9)(10)(11). Unfortunately, Barrett's carcinoma shows a very heterogenous behavior in progression and response to neoadjuvant chemotherapy.…”
mentioning
confidence: 99%
“…After the staging, potentially operable patients either proceeded directly to oesophageal resection or received 5-fluorouracil-based neoadjuvant polychemotherapy preoperatively [14]. All patients staged as having tumours potentially resectable for cure were offered surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Doch das Karzinom wird bei über der Hälfte der Patienten im fortgeschrittenem Stadium (UICC III/IV) diagnostiziert und die Chance auf eine vollständige Entfernung des Tumors sinkt. Von diesen Patienten werden weniger als 60% kurativ reseziert [19].…”
Section: Die Mortalität Ist Unverändert Hoch Am Magenkarzinom Sterbeunclassified
“…Die 5-Jahres-Überlebensrate (5-JÜR) liegt bei 40-50% in den westlichen Ländern und Japan [14,19,35,59]. Unter kurativer Therapieintention haben frühe Stadien, UICC Ia und Ib, eine 5-JÜR von 83% und 69% sowie 43% im UICC-Stadium II; bei fortgeschrittenen Tumorstadien sinkt sie erheblich und liegt zwischen 28% (UICC III) und 8,7% (UICC IV) [19,33,56,57] [27].…”
Section: Die Mortalität Ist Unverändert Hoch Am Magenkarzinom Sterbeunclassified